THE DIFFERENCE OF RISK FACTORS OF ACUTE UPPER RESPIRATORY TRACT INFECTION IN THE URBAN AND RURAL PUBLIC HEALTH CENTER SEMARANG - Regina Islamia Mugopal; Anna Mailasari Kusuma Dewi; Galuh Hardaningsih; Teddy Wahyu Nugroho (JURNAL KEDOKTERAN DIPONEGORO (DIPONEGORO MEDICAL JOURNAL), 2021)
Abstract Background: The acute upper respiratory tract infection was an infection on respiratory tract organ from the nose until pharynx. The geographical condition of a region could affect the case of acute upper respiratory tract infection. The factors related to both urban and rural life could affect in the difference of respiratory condition. The biological change of age, nutritional status, and allergy status were highly related to the increase of respiratory condition.Aim: To identify the risk factors of acute upper respiratory tract infection in the urban and rural public health center of Semarang.Methods: This research exerted observational research design and cross-sectional method. The total of research subjects were 200 patients with the diagnosis of acute upper respiratory tract infection in both the urban and rural public health center of Semarang. The risk factors were comprised of age, gender, body height, body weight, and history of drug allergy. The data sampling was taken through consecutive sampling technique. Moreover, the statistic test used Chi-square test.Results: This research finding referred that the largest number of sample on the age category in both urban and rural public health center were in the adult age (20-60 years old) with percentage of urban public health center (66,5%) and rural public health center (46%). The risk factor of age indicated a significant result in the urban public health center (p = 0,000) and rural public health center (p = 0,010). Next, the risk factor of gender indicated an insignificant result in the urban public health center (p = 0,391) and rural public health center (p = 0,885). Last, the risk factor of nutritional status in the urban public health center indicated an insignificant result (p = 0,094), while in the rural public health center indicated a significant result (p = 0,006).Conclusion: The risk factors of acute upper respiratory tract infection in rural public health center was different from the risk factors in urban public health center. The risk factors of acute upper respiratory tarct infection in the rural public health center were age and nutritional status, while the risk factor of acute upper respiratory  tract infection in the urban public health center was age.